USE OF AGROMINERAL AS SUBSTRATE FOR GROWTH OF EUCALYPTUS SEEDLINGS - Silva, Rafael Cipriano da; Beneton, Karen; Ieda, João José Cardinali; Azevedo, Antonio Carlos de; Pereira, Marcos Gervasio (Floresta, 2022)
Success in the production of eucalyptus seedlings directly affects the development of plants in the field. Several factors influence their initial growth, especially the substrate. This study aimed to evaluate the growth of Eucalyptus globulus seedlings and characteristics of the substrate using silicate agromineral (SA) in different proportions (substrate:SA; v/v): T0 – 100:00%, T1 – 90:10%, T2 – 80:20%, and T3 – 50:50%. The treatments were evaluated using a completely randomized design. Measurements of height (H), stem diameter (SD) and calculation of the H/SD ratio of the plants were performed every 3 weeks, totaling 4 measurements. At the end of the experiment (12 weeks), soil fertility analyses, granulometric analysis (sand, silt and clay) and total chemical analysis were carried out. Due to the chemical and mineralogical composition of SA, its use in substrate in a greater proportion (T3) promoted the increase of exchangeable K, Ca and Si contents, which influenced the increase in the sum of bases and cation exchange capacity. The levels of assimilable P and micronutrients Fe, Cu, Zn and Mn were also higher in this treatment. The increase in SA proportions in the substrate composition also favored increase in the sand fraction and reduction in the clay fraction. As for the growth of seedlings, the results were not significant for H and SD as a function of SA doses, leading to the conclusion that the solubilization and slow release of nutrients by SA did not influence the growth of the plants